Study of "time-lag" of occupant behavior occurrences for establishing an occupant-centric building control system. (15th May 2022) - Li, Canjun; Zhu, Han; Lian, Xiangchao; Liu, Yuxin; Li, Xiaohan; Feng, Yanbo
Abstract: To achieve occupant-centric building and occupant-centric control (OCC) logic for an environmental control system (ECS, such as lighting, shading, and HVAC), operational strategies should consider occupant behavior (OB) characteristics to meet the dynamic indoor environment preferences and adjustment habits of occupants. Using shading behavior as an example, the "time-lag" of OB occurrences was proposed and studied. Occupants often have a certain tolerance to changes in the surrounding environment, which corresponds to the lag time from the stimuli occurrence to the behavior occurrence. By considering this characteristic, an advanced OB prediction model (OBPM-ARDL) was proposed, resulting in an 11% accuracy improvement in OB prediction. Furthermore, after deducing the concept of "sensitive position of behavior (SPB)" and "insensitive position of behavior (IPB)" to describe the dynamically distribution of office room's occupancy, an OCC logic to operate an ECS that meets the requirements of building energy savings and visual and thermal comfort was derived. Highlights: The "time lag" of behavior occurrence is proposed and quantified. Relationship between occupants' distribution and behavior frequency is described. Occupant-centric control logic on 2 occupant behavior characteristics is discussed.